Nickel Nanowire@Porous NiCo2O4 Nanorods Arrays Grown on Nickel Foam as Efficient Pseudocapacitor Electrode - Wan, Houzhao; Li, Lang; Zhang, Jun; Liu, Xiang; Wang, Hanbin; Wang, Hao (Frontiers in Energy Research, 2017)
A three dimensional hierarchical nanostructure composed of nickel nanowires and porous NiCo2O4 nanorods arrays on the surface of nickel foam is successfully fabricated by a facile route. In this structure, the nickel nanowires are used as core materials to support high-pseudocapacitance NiCo2O4 nanorods and construct the well-defined NiCo2O4 nanorods shell/nickel nanowires core hierarchical structure on nickel foam. Benefiting from the participation of nickel nanowires, the nickel nanowire@NiCo2O4/Ni foam electrode shows a high areal specific capacitance (7.4 F cm-2 at 5 mA cm-2), excellent rate capability (88.04% retained at 100 mA cm-2) and good cycling stability (74.08% retained after 1500 cycles). The superior electrochemical properties made it promising as electrode for supercapacitors.